French Defense Policy in 2022-2024: Changes within Continuity - A. Yu. Chikhachev (Сравнительная политика, 2024)
This article delves into French contemporary defense policy beginning with the President Emmanuel Macron’s 2022 statements about transitioning to a so-called “military economy.” Since then, the French government has indeed put defense at the top of its priorities taking various steps both within the national borders and in the international arena. The research aims to identify the main characteristics of French defense policy at this stage. Relying on strategic documents and statistical data, the author analyzes the extent of the shifts in three dimensions, including doctrinal, industrial, and operational. Specifically, the study has established that neither the 2022 Strategic Review nor the 2024-2030 Military Planning Law demonstrates any intention to abandon the complex armed forces model despite its shortcomings, or to revise the spectrum of allied partnerships. The increase in the defense budget (doubling in annual terms, accounting for the 2019-2025 law also) is mainly explained by preparations for the planned modernization of the nuclear arsenal. At the same time, French conventional forces will not experience a significant increase, either in personnel numbers or in arms and equipment. Finally, since 2022, there has been no fundamental revision of the military presence in various regions of the world. In the Middle East and the Asia-Pacific, the presence of French forces remains at its previous level; in Western Africa, a reassessment of functions for the deployed contingents is underway without any intention to leave the continent at all. On the European theater there is a gradual buildup of capabilities, which is not so substantial in absolute terms and implemented in correspondence with NATO’s general guidelines. As a result, the article concludes that, despite all the slogans about a new «military economy,» there is still a strong continuity in France’s defense policy; some new features do take place, but the model of military development itself has remained unchanged. The most likely prospect is the continuation of this course, including the deepening of Paris’ ties with partners in the framework of NATO and its global partners, at least until the next presidential elections in 2027.